Wpływ katastrofy czarnobylskiej na proces kształtowania ukraińskiej opozycji antykomunistycznej w Związku Sowieckim .......... 207 - Sekuła, Paweł (Tożsamość i pamięć : konteksty kulturowe i społeczne. Studia ukrainoznawcze, 2021)
THE INFLUENCE OF THE CHERNOBYL DISASTER ON THE PROCESS OF SHAPING THE UKRAINIAN ANTI-COMMUNIST OPPOSITION IN THE SOVIET UNIONThe presented issue regards the influence of the Chernobyl disaster on the formation of Ukrainian anticommunist organizations and the development of patriotic attitudes in the Ukrainian society in 1986-1991. The article describes the reaction of the Ukrainian SSR citizens to communist propaganda after the nuclear explosion, as well as the Soviet government’s attempts to disseminate the regime’s version of events in Chernobyl. From the point of view of the social-national mobilization of Ukrainian people, political methods of dissent assumed by the anti-communist opposition were essential. Particular attention was paid to the way of interpretation of the nuclear disaster assumed by the representatives of Chernobyl organizations consisting of liquidators, victims of the nuclear power plant accident, and members of the ecological and cultural movements groups established in Ukraine after 1986.